2010
DOI: 10.1177/230949901001800105
|View full text |Cite
|
Sign up to set email alerts
|

Lower-Limb Alignment and Posterior Tibial Slope in Pakistanis: A Radiographic Study

Abstract: Knee alignment and geometry vary in different population subsets. With regard to total knee arthroplasty, the more medially inclined angle J in Pakistani men suggests that an anteroposterior cut of the distal femur should be in increased external rotation, compared with Pakistani women. Whereas the greater posterior tibial slope in Pakistanis suggests that a proximal tibial cut with a greater posterior tibial slope may reduce the chance of tibial loosening and increase postoperative knee range of motion, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 14 publications
7
40
0
Order By: Relevance
“…However, it is not feasible to compare our findings directly with those of previous studies because of differences in age and sex compositions of populations studied, the types of parameters measured, and the types of variables reported [11,16,26,29,30,36,38,40]. Nonetheless, it appears that like the Korean female patients in this study, Asian (Chinese, Indian, and Japanese) patients undergoing TKA for medial osteoarthritis commonly exhibit lateral femoral bowing and varus condylar orientation and a larger tibial plateau inclination than healthy Western subjects (Table 7) [11,26,29,30,36,40].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…However, it is not feasible to compare our findings directly with those of previous studies because of differences in age and sex compositions of populations studied, the types of parameters measured, and the types of variables reported [11,16,26,29,30,36,38,40]. Nonetheless, it appears that like the Korean female patients in this study, Asian (Chinese, Indian, and Japanese) patients undergoing TKA for medial osteoarthritis commonly exhibit lateral femoral bowing and varus condylar orientation and a larger tibial plateau inclination than healthy Western subjects (Table 7) [11,26,29,30,36,40].…”
Section: Discussionmentioning
confidence: 89%
“…This 3°of varus inclination of the tibial plateau and approximately the same degree of valgus orientation of the distal femoral condyle have been viewed as basic in past anatomical studies [11,26] and as the norm to achieve proper coronal alignment using most TKA instrumentation systems. However, several authors have reported considerable variations in normal alignment between ethnicities [16,29,30,36,40]. Furthermore, several Asian studies have found femoral lateral bowing and obliquity of the proximal tibial joint surface in knees with advanced osteoarthritis can present with more severe varus inclination ([ 3°) [16,29,30,36,40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tang et al [9] in an analysis of 50 normal Chinese adults have reported a mean mechanical alignment of 177.8°or 2.2°varus. In a similar study involving 59 normal Pakistani adults, Khattak et al [10] have reported a mean mechanical alignment of 178.9°or 1.1°varus. However, both these studies have not analysed variations in normal mechanical alignment and the factors which may contribute to this variation.…”
Section: Introductionmentioning
confidence: 94%
“…Almost all studies in this field have been done in the Caucasian population. Studies done in the Chinese, Japanese, and Pakistani populations (Asians) have documented a difference in the PTS in their respective population from the Caucasians 68. Considering these racial differences in the anatomy of the knee, the postoperative outcome and the need for a difference in the prosthesis according to racial variations, a study was needed to bring out the characteristics of Indian population, which would help in designing prosthesis suited for Indian population.…”
Section: Introductionmentioning
confidence: 99%